Empowerment of Religious Potential for Poverty Alleviation in Agrarian Areas - Muhamad Hanif Fuadi (Yayasan Adra Karima Hubbi, 2024)
This study examines the role of empowering religious potential in efforts to alleviate poverty in agrarian areas, with a case study in Jayagiri Village, Lembang District, West Bandung. Using a qualitative approach with a case study method, this study reveals how religious values and institutions can be integrated into rural economic development strategies. The results of the study show that the empowerment of religious potential contributes greatly to improving community welfare through strengthening social capital, work ethics, and community-based economic empowerment.